MATRINE INHIBITS PROLIFERATION AND INVASION OF MOUSE CT26 COLON CANCER CELLS VIA THE P62/PARKIN/PINK1 MITOPHAGY PATHWAY - Nanyang Li; Feng Wang; Chunmei Li; Xuejun Zhang; Lian Li; Jingjing Liang; Fengqiang Wang (Journal of Animal and Plant Sciences, 2026)
<span style="font-size: 10.0pt; mso-bidi-font-size: 11.0pt; line-height: 115%; font-family: 'Times New Roman',serif; mso-fareast-font-family: SimSun; mso-fareast-theme-font: minor-fareast; color: black; mso-themecolor: text1; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: ER;">Matrine, an alkaloid extracted from Sophora flavescens, has been shown in recent studies to inhibit colorectal cancer (CRC) progression by regulating mitophagy pathway. This study aimed to investigate whether Matrine affects proliferation of mouse CT26 colon cancer (CC) cells through p62/Parkin/PINK1 signaling axis. CT26 cells were treated with matrine in various concentrations, and proteins related to proliferation, apoptosis, invasion, and epithelial-mesenchymal transition (EMT) was detected. A CT26 tumor-bearing mouse model was fabricated, and mice were rolled into model, positive control, and low-, medium-, and high-dose matrine groups. Tumor weight, inhibition rate, and microvessel density (MVD) were compared, and the expression of EMT and p62/Parkin/PINK1 pathway proteins was examined. Matrine concentration-dependently inhibited cell proliferation, invasion, and cloning, promoted apoptosis, up-regulated E-cadherin, Parkin, and PINK1, and down-regulated N-cadherin, Vimentin, Snail, and p62. In the mouse model, matrine significantly reduced tumor weight and MVD and regulated the expression of the aforementioned proteins. Matrine exerts its anti-CC effects by activating p62/Parkin/PINK1-mediated mitophagy, which induces tumor cell apoptosis and suppresses EMT and angiogenesis. A theoretical basis for understanding mechanism of matrine and its clinical application in treating CC was provided.
Keywords: colon cancer; matrine; proliferation; invasion; EMT; p62/Parkin/PINK1 signaling; mice